Music theory: problems and practices in the middle ages and renaissance - Ultan, Lloyd (Minneapolis University of Minnesota Press, 1977)
Music Theory was first published in 1977.This is a textbook for the study of music theory, using a historical approach which enables the student to learn about compositional devices as they appeared and evolved in early Western music. The textbook and its accompanying workbook provide for the study of basic analytical and compositional techniques through the use of selected literature and original compositional techniques through the use of selected literature and original compositional assignments. With these teaching materials techniques which have been employed periodically throughout history, even into the most advanced of contemporary composition, may be mastered and absorbed as an integral part of the students understanding of the aesthetic principles of art. Such compositional techniques as canon, cadential patterns, isorhythm, cantus firmus, initiation, and invertible counterpoint are among the many which are presented for study.A unique feature of the text is the introduction and employment of early notations. Including this dimension helps the student to understand the limitations imposed by the graphic tools of the composer upon his compositional decisions. This approach also enables the student to develop flexibility in the interpretation of notation.The book has been used in a preliminary form by hundreds of students and many different types of teachers. The students were typical college freshmen and sophomores, and none of the faculty had special training in the music of the periods studied, since any teacher with conventional theoretical training can easily master and present the material.The workbook contains 68 musical examples, and specific assignments for students are correlated with the textbook material.